The Effect of Foliar Potassium and Seaweed Products in Combination with a Leonardite Fertigation Product on Flame Seedless Grape Quality - Strydom, J. (South African Journal of Enology and Viticulture, 2016)
Berry colour and size are important factors determining Flame Seedless quality. Supplementary to standard cultivation, foliar application of potassium (K) and seaweed or soil application of vegetable extracts affect grape quality. The purpose of this trial was to determine if combined product application (CPA) of K, seaweed and leonardite (organic material of vegetable origin) can improve Flame Seedless grape colour, berry size and composition. This study was conducted on Flame Seedless in the Berg River Valley in two seasons. In 2011/2012, leonardite was applied through fertigation six, four and three weeks before harvest, while K and seaweed were applied as foliar sprays four and three weeks before harvest. In 2012/2013, all products were applied eight and six weeks before harvest. Treatments included (1) control (ethephon/ ethephon and abscisic acid – ABA); (2) CPA with ethephon/ethephon and ABA (CPA-plus); and (3) CPA without ethephon/ethephon and ABA (CPA-minus). All vines received standard gibberellic acid treatments. Berry quality was determined. In 2011/2012, CPA-minus reduced anthocyanin concentration significantly compared to the control. CPA-plus increased berry diameter significantly compared to the control on the first harvest date in 2012/2013. Compared to the control, CPA-plus significantly increased total soluble solids (TSS) on all harvest dates in 2011/2012, and on the first harvest date of 2012/2013. Compared to the control, CPA-plus did not improve colour, but it retarded total titratable acidity breakdown in both seasons. Ethephon/ethephon and ABA must be applied for acceptable colour. The consistent effect on TSS shows the ability of CPA-plus to enhance Flame Seedless ripening.